Associations Between Depressive Symptoms and Religiosity in Young Adults - Gwin, Shannon (Journal of religion and health, 2020)
The purpose of this study was to evaluate the association between religiosity and depressive symptoms among young adults, as well as determine whether possession of parental assets influences the relationship between religiosity and depressive symptoms. Young adults (n = 775) from universities in the southwest were sent an online survey, evaluating depressive symptoms, religiosity beliefs, and the protective assets of the relationships with their mother and father. With regard to young adult depressive symptoms, results showed a significant inverse association with levels of organizational religious activities (OR range = 0.208-0.555), levels of non-organizational religious activities (OR range = 0.282-0.399), and intrinsic religiosity (OR range = 0.216-0.489). Overall, religiosity beliefs and practices appeared to be associated with fewer depressive symptoms. Inclusion of religious/spirituality-oriented strategies may be important for mental health interventions in emerging adulthood.